Custom, Power and the Power of Rules : International Relations and Customary International Law. - Byers, Michael (Cambridge University Press, 1999)
This book sets out to explain the most foundational aspect of international law in international relations terms. By doing so it goes straight to the central problem of international law - that although legally speaking all states are equal, socially speaking they clearly are not. An ambitious and controversial book.